The carbon cost of an educated future: A consumer lifestyle approach - Ethan J. Sharygin (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2013)
Demographic and economic growth will account for most of the anticipated growth in greenhouse gas (GHG) emissions in the next century. Education is associated with development, and the world population in the near future is likely to be significantly better educated than today. Previous studies of household energy demand and associated emissions have not directly considered the consequences of a more educated population. In this study, I estimate the energy intensity of consumption dollars and the total impact of households according to their demographic characteristics, with particular attention to differences in spending habits by education and the environmental consequences. I find that education results in fewer emissions per household, holding other household characteristics constant. Each year of education is associated with an average effect in CO2-equivalent (CO2e) emission of -466kg/yr. After controlling for household characteristics, the effect of a year of education is -163.1kg per year. Educated households spend less on home energy and transportation by car, two of the most important sources of household level atmospheric GHG production. They spend relatively more on investment goods, public transport, and other activities which have a low environmental footprint.
Keywords: 330; human capital; environmental impact; household emissions